Human relations in organizations applications and skill building - Lussier, Robert N. (New York, NY McGraw Hill LLC, 2022)
"Human Relations in Organizations 12th edition, is designed to be flexible enough to be used with the traditional lecture method while offering a wide range of engaging in-class and online activities"--
Revised edition of the author's Human relations in organizations, [2018]
Includes Glossary (531-535) and index
Keywords: Interpersonal relations; Organizational behavior